Efeito do exercício físico em ratos submetidos à dieta padrão restrita no tempo de ingestão e sacarose: metabolismo energético e estresse ocidadtivo - Barbanera, Pedro Octavio [UNESP] (2014)
Sedentary lifestyles and poor dietary habits, such as restrictive diets hypercaloric are relevant factors to be considered. This contemporary life style, which restricts the time spent on diet and physical inactivity, especially those related to cardiovascular. To prevent or even mitigate these effects, the frequent recommendation has been the practice of physical exercise as a measure of therapeutic interaction in preventive medicine and rehabilitation. Thus, the aim of this study was to evaluate the effects of physical exercise in rats subjected to restrictive diets hypercalorific through metabolic, nutritional, morphometric and colorimetric parameters in addition to oxidative stress in cardiac tissue. 32 Winstar rats, males, 45 days old were used. Animals were divided into two groups: G1 (n=16) as the control, received food and water ad libitum, G2 (n=16) received a diet restricted in time and 30% sucrose solution ad libitum. G2 animals received the same amount of feed ingested by G1, offered in a limited time of 2 hours a day during the period of 30 days, which is considered pre-training. After this period, the two groups (G1 and G2) were subdivided (n=8), G3 receiving the same treatment as G1 and animals in this group were considered inactive and G4 received the same treatment and G2 were considered trained. G1 and G2 were maintained in the training phase. The swimming was used as a model of exercise with moderate intensity training for 8 weeks (training phase). The experimental design was completely randomized with 32 treatments and 8 replications, with a significance level of 5% probability. Dietary intake was higher in G1 and G3 and lower in G2 and G4, the same occurred for liquid consumption. Calorimetry reveals lower carbohydrate oxidation and increased lipid oxidation with high activity of β-hidroxacil-CoA dehydrogenase in G2. These animals also had higher glucose, lower HDL - cholesterol and abnormal accumulation of ...